2013
DOI: 10.1016/j.toxicon.2012.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase from the venom of the social wasp Polybia paulista (Hymenoptera, Vespidae): Cloning, structural modeling, purification, and immunological analysis

Abstract: In this study, we describe the cDNA cloning, sequencing, and 3-D structure of the allergen hyaluronidase from Polybia paulista venom (Pp-Hyal). Using a proteomic approach, the native form of Pp-Hyal was purified to homogeneity and used to produce a Pp-specific polyclonal antibody. The results revealed that Pp-Hyal can be classified as a glycosyl hydrolase and that the full-length Pp-Hyal cDNA (1315 bp; GI: 302201582) is similar (80-90%) to hyaluronidase from the venoms of endemic Northern wasp species. The iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 39 publications
0
47
0
Order By: Relevance
“…This difference may be a result of unpredicted weight of post-translational modifications, such as N-glycosylation. Feng et al [52] and Jacomini et al [43] also showed similar differences among deduced and experimental hyaluronidases from Mesobuthus martensii (scorpion) and Polybia paulista (wasp) venoms. As glycosylation is the most common post-translational modification of many eukaryotic intracellular proteins, deglycosylation analysis revealed that N-glycosylation is the most frequent glycosylation type in the hyaluronidase from M. martensii venom [52].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This difference may be a result of unpredicted weight of post-translational modifications, such as N-glycosylation. Feng et al [52] and Jacomini et al [43] also showed similar differences among deduced and experimental hyaluronidases from Mesobuthus martensii (scorpion) and Polybia paulista (wasp) venoms. As glycosylation is the most common post-translational modification of many eukaryotic intracellular proteins, deglycosylation analysis revealed that N-glycosylation is the most frequent glycosylation type in the hyaluronidase from M. martensii venom [52].…”
Section: Discussionmentioning
confidence: 68%
“…Ts hyaluronidase sequences were aligned with known hyaluronidase sequences from diverse organisms, including Mesobuthus martensii (GenBank: ACY69673; [52]), Loxosceles intermedia (GenBank: AGH25912; [42]), Brachypelma vagans (GenBank: AFS33217; [41]), Polybia paulista (GenBank: ADL 09135; [43]), Apis mellifera (UniProtKB/Swiss-Prot: Q08169; [53]), and Homo sapiens (UniProtKB/Swiss-Prot: Q12794; [54]). A multiple alignment was performed using the algorithm Clustal W in MEGA 5.1 software [55].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyaluronidase also speeds up the spreading and absorption of the venom's toxin component. Hyaluronidases are found in all types of animal venoms with many isoforms (Girish et al, 2004;Justo Jacomini et al, 2013;Kudo and Tu, 2001;Pukrittayakamee et al, 1988;Wahby et al, 2012). All hyaluronidases act as "allergenic factors" and are able to induce severe and fatal anaphylactic IgE-mediated reactions in humans.…”
Section: Profiles Of Venom Proteins Proportion Of Protein Componentsmentioning
confidence: 99%
“…All hyaluronidases act as "allergenic factors" and are able to induce severe and fatal anaphylactic IgE-mediated reactions in humans. Moreover, they are suggested to be essential for the paralytic activity of venom Baek et al, 2013;Justo Jacomini et al, 2013. There are at least two types of hymenoptera hyaluronidase: A (or a) and B (or b).…”
Section: Profiles Of Venom Proteins Proportion Of Protein Componentsmentioning
confidence: 99%